Groundwater markets and water use efficiency: the case of Karnataka - Deepak, S. C.; Chandrakanth, M.G.; Nagaraj, N. (International Water Management Institute, 2005)
Research highlight based on a paper titled ?Groundwater markets promoting efficiency in water use in agriculture in Karnataka.?